PANCASILA DALAM PENDIDIKAN AGAMA - Listia Suprobo (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2020)
Pancasila is a format of values ​​that become a reference in viewing and managing life with the Indonesian people. The founders of the nation explored the values ​​of Pancasila from the daily life of the nation that existed in the archipelago before the establishment of the modern Indonesian state. because the values ​​that exist in Pancasila are also found in the existing value system of religions and cultures of the people of the archipelago, therefore Pancasila is a meeting point between all differences. Religious education in each religion is unique, as is the uniqueness of each religion in relation to religious institutions, social and political institutions. Religions also have their own histories which then shape the uniqueness of the teaching format. However, there are things that are more or less the same, in all types of religious education, which can then be called the values ​​of the common good that exist in all religions. These values ​​of the common good, as well as Pancasila, are the meeting point in all religious education. Pancasila in religious education is very important to be articulated, because all religious people will live in the same public space in many situations and conditions. Religious education builds self-awareness of the people and their relationship with God in accordance with the construction of knowledge and various expressions of faith. Dogmatically formulated claims of sanctity and salvation often leave little room for tolerance of doctrinal differences. In dogmatic reasoning, it is as if the public sphere will be privatized or adapted to the relevant teachings. This is where intolerance becomes a potential that exists in all religious dogmas. However it differs in the aspect of values, which lead to reflection and awareness that is open to life, the wisdom of tolerance which is very useful for building a common life. The problem is how the implementation of Pancasila in religious education will be carried out? First of all, there is a dialogue on how to view the relationship between religion and Pancasila. Closed dogmatic thinking needs to be criticized by reflecting on the values ​​and history of religious thought need to be seen critically in the context of space and time. So in favor of values humanity becomes a way of dialogue with life and the manifestation of faith that answers life's challenges. Placing Pancasila in religious education means using a humanist-religious educational framework, because from there human values ​​will be easily realized, dialogued and fostered creativity to build a community life that upholds peace and human dignity.